Awareness of Source of Radiation, Its Hazards and Protection among Final Year MBBS Students: A Cross-sectional Observational Study - DIPSA DIGANT SHASTRI; NEHAL SANKET DIWANJI; MONA DIGANT SHASTRI; EKTA J DESAI; PARESH GORDHANBHAI PATEL; NIRAV KISHORBHAI KADWANI; NIPA PATIDAR; AVANI YOGESHBHAI BHATT (International Journal of Anatomy Radiology and Surgery, 2021)
Introduction: Increase availability of multi-detector high speed CT scan, digital radiography and various image guided interventional procedures has increased the total number of radiation related examinations in current era. These have lead to increase radiation exposure to patients as well as the radiologist. This situation has raised the concern about the potential side effects to patients, like radiation-related cancer and death. Aim: Evaluation of awareness of source of radiation, radiation hazards and radiation protection among final year medical students in Tertiary Care Medical College Hospital. Materials and Methods: This was a cross-sectional observational type of study in which total 136 final MBBS students were issued a questionnaire consisting of 12 multiple choice questions including demographic data, awareness about source of radiation, radiation hazard, protection issues and knowledge about radiation dose levels of common radiological examinations. All questions were multiple choice types with answers containing 2 to 9 choices having only one correct answer. The questionnaire was prepared by authors and their answers were validated by various faculties of Department of Radiodiagnosis by peer review methods. This questionnaire was given in a physical form. The obtained data were analysed using statistical software (descriptive statistics used). As homogenous group of final year medical students were analysed, no scoring and no statistical test were needed. Results: In present study 87.5 % (n=119) of students considered radiation knowledge important for them. Out of eight specific questions for checking their knowledge about radiation awareness, five questions were regarding safe radiation practice, radiation exposure, and radiation dose in common and radiological examination. Among these questions “Rule of 10”- question was correctly answered by 113 (83.1%) of students. Questions regarding “Radiological examination of pregnant patient”- was correctly answered by 114 (83.8 %) of students and “Radiation exposure to patients during diagnostic radiology” question was correctly answered by 115 (84.6%) of students. Conclusion: Medical students have good awareness about radiation protection, with a specific gap of knowledge concerning source of radiation, biological effect of radiation and radiation hazards. Undergraduate teaching curriculum must include comprehensive knowledge about radiation hazards and radiation safety.